Kerja Sama Indonesia-Singapura di Bidang Ekonomi Digital melalui Pembentukan Kawasan Ekonomi Khusus Nongsa Digital Park di Batam (2018-2020) - Geraldo, Varelza (Universitas Sulawesi Barat, 2022)
Abstract: This research was conducted to determine the realization of the digital economy cooperation agreement between Indonesia and Singapore regarding the Nongsa Digital Park Special Economic Zone in Batam, in this study the author describes how the realization and the opportunities and challenges of the two countries in collaborating in the digital economy sector, as well as outlining the conditions of the digital economy in Indonesia before and after the bilateral cooperation agreement. The research method that the author uses is a qualitative method with a descriptive analysis approach and uses techniques to collect data from primary sources, namely in the form of interviews and secondary data, namely in the form of data obtained through literature studies, in the perspective of international relations, namely with a focus on discussion in the field of bilateral cooperation. This research shows the results of the Indonesia-Singapore bilateral cooperation agreement in the digital economy through the realization of the Nongsa Digital Park Special Economic Zone on Batam in March 2018.Keywords: Digital Economy, Special Economic Zones, Bilateral Cooperation, Realization, Nongsa Digital Park